Radiological and histological findings in ancient salt mummies from the salt mine of Douzlākh, Iran. - Lena Maria Öhrström; Herman Marquez; Roger Seiler; Beata Bode; Abolfazl Aali; Thomas Stöllner; Frank Jakobus Rühli (PLoS ONE)
Computed tomography studies and histological analyses were performed on the mummified remains found in the Chehrābād salt mine in northwestern Iran. The ancient salt mummies are dated to the Achaemenid (550-330 BC) and Sassanid (3rd-7th century AD) time period and died in mining incidents. The aim of the study was to describe the radiological and histological findings of several ancient Iranian salt mummies with special interest in pathological and postmortem changes. The mummified remains show multiple traumatic alterations, such as fractures and signs of massive compression. Histological analyses can clearly differentiate soft tissue, however the preservation status is variable. These Iranian salt mummies are a rare example of the ancient Iranian population. The soft tissue and organs are well preserved, however in different degrees due to the varying conditions.